2½-D inversion constraints on the palinspastic retro-deformation of Siluro-Devonian structures in the Black Range region, western Victoria - the "Crab Nebula" untangled. Issue 1 (1st December 2016) - Skladzien, Phil; McLean, Mark; Cayley, Ross; Taylor, David
Abstract : The Stavely Arc developed during the Cambrian above a continent (west) dipping subduction zone within the Grampians-Stavely Zone in present-day western Victoria. Siluro-Devonian regional dextral trans-tensional strike-slip faults recently mapped by the Geological Survey of Victoria in Cambrian basement, previously only recognised in Grampians Group cover, have segmented what was a relatively simple Cambrian configuration of Stavely Arc volcanic fault slices into a complex array of segmented and variably rotated arc fragments, including the until now enigmatic "Crab Nebula" in the Black Range. Inversion of magnetic data has provided an understanding of the 3D geometries of the three volcanic belts in the Black Range. Applying this understanding, together with over-printing criteria evident in filtered potential field data, within the context of a trans-tensional strike-slip stress regime, has enabled a retro-deformation of the Black Range belts into a single, west dipping belt of arc volcanics - an untangled, pre-Silurian "Crab Nebula". The proven prospectivity of the Black Range Belt (by the presence of the McRaes/Eclipse prospect) can now be extended to all three of the Black Range belts.